Constitutional law and human rights in Malaysia: topical issues and perspectives - Mokhtar, Khairil Azmin (Thomson Reuters (Sweet & Maxwell) Malaysia (Sdn Bhd), 2013)
The constitution of a country is the embodiment of the nation’s philosophy and history, amalgamating the agreed basic principles governing relationships between individuals, the society and the government. Since independence, the Federal Constitution of Malaysia has catered to the needs of the diverse Malaysian population. Over the course of time and with the rapid changes that have taken place in the various spheres of life, several issues have arisen the resolution of which requires the constitutional law of the country to grow and develop in tandem. This book addresses a wide range of topical and important issues which concern the Malaysian public today. Through 28 chapters arranged in three parts, this book covers topics pertaining to the principal organs of government, the basic concepts and features of the Constitution, and human rights. It contains an interesting compilation of materials authored by a panel of contributors with wide and varied experience of constitutional law, comprising senior and young scholars from various tertiary institutions within the country as well as a few scholars from other jurisdictions. The discussion contained in the book is enlightening, analytical as well as thought-provoking. Besides stating the applicable principles of constitutional law clearly, the book addresses challenging issues faced by the Malaysian society and provides legal solutions as well as suggestions for the future development of constitutional law in Malaysia. Covering issues such as freedom of speech and expression, the accountability and integrity of the judiciary, the price of access to justice, the electoral process, elected members and the right to change party, the rights of the orang asli, freedom of communication and the Internet, the legal protection of the right to privacy as well as the rights of women in Malaysia, this book presents constitutional in Malaysia from a different and fresh perspective.